Legal regulation of the right of common property in accordance with the civil legislation of the Republic of Uzbekistan - Musayev Elbek Tayufovich (Genius Journals, 2023)
The article discusses the features of the legal regulation of the right of common property under the civil legislation of the Republic of Uzbekistan - the definition of the right of common property is given, the grounds for the emergence of the right of common property and the legal status of subjects of the right of common property are considered, the objects of the right of common property are defined. Depending on the nature of internal relations between co-owners, two types of common property are analyzed: shared and joint. The definition of a share in common property is considered.
Keywords: common property right; shared property; joint property; legislation